Advances in Fire Retardancy of Polymeric Nanocomposites and Applications - Ezika, Anthony Chidi; Kupolati, Williams Kehinde; Sadiku, Emmanuel Rotimi; Idumah, Christopher (Journal of Research Updates in Polymer Science, 2025)
Emerging advancement in nanotechnology have facilitated the embedment of nanomaterials (NMs) such as graphene and derivatives, carbon nanotubes and derivatives, nanowires, and so on, within polymeric matrices to attain enhanced properties, especially fire retardancy, in polymeric nanoarchitectures (PNC) for multifarious applications. In thermal interface materials (TIM) for electronic gadgets, notable fire hazards are often ignored, whereas PNC exhibiting electromagnetic interference (EMI) shielding are frequently subjected to accidental fires. Furthermore, fire warning sensors with capability of rapidly exposing fire dangers in combustible materials plays a key role in mitigating or entirely eliminating fire disasters in most scenarios. Moreover, the escalating evolution of electronic gadgets in the fifth-generation (5G) era has made superlative fire safety, thermal stability and high-performance of PNC highly imperative. Nanowires are one-dimensional (1-D) nanostructures possessing a high length to diameter aspect ratios, unique flame retardant (FR), mechanical, electrical, thermal, and optical properties. The inclusion of different forms of nanowires within polymeric matrices has tremendously enhanced the flame retardancy (F-R) of nanowire@polymeric nanoarchitectures (N-PNC) thereby enlarging their scope of applications. Therefore, this paper presents advances in flame retardancy of nanowire polymeric nanoarchitectures.